The Rise of Incompetence - Grudin, Jonathan (ACM Interactions, 2016)
We should be enjoying a golden age of competence. We have access to so much information. YouTube videos show us how to do almost anything. And there are impressive achievements: Automobiles run more efficiently and last longer; products are rapidly distributed worldwide. Nevertheless, there is a sense that the world isn’t running that smoothly. Inept governments and poor service are common. Financiers whose ruinous actions led to worldwide recession didn’t lose their jobs. In HCI, many nod when Don Norman says, “UI is getting worse—all over.” How could incompetence be on the rise when knowledge and tools proliferate?